DESIGN RECOMMENDATIONS FOR BUILDINGS IN CHENNAI USING MAHONEY TABLE - Kavitha Suresh; Suresh Ramamurthy (International Journal of Innovations in Engineering Research and Technology, 2022)
In the current scenario, the necessity of sustainable living environment is the essential need of the hour. The recent expansion of the Chennai metropolitan area as a Greater Chennai Corporation by inclusion of suburban zones makes it as one of the fastest growing cities. In addition to that Chennai city developed more infrastructure development in almost all areas that also includes “smart city” project. These types of infrastructure development lead to various climatic issues bringing negative impact on the environment leading to blocking of gifts of nature like air, wind, water. However, we cannot give up development of city since it is economically essential for the development of industries which totally depends on manual labour who are to be accommodated in these building structures. This does not mean that we can compromise with the natural environment. Even in the past, our earlier generations were aware of the benefits from certain climatic features by adopting appropriate building design. This paper gives an intuition into the design recommendations for climatic design approaches for the city of Chennai through Mahoney calculation.